2021
DOI: 10.3389/fclim.2021.580556
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of User Needs and Perceptions Related to Sub-Seasonal and Seasonal Forecasts on Farmers' Decisions in Kenya: A Systematic Review

Abstract: One major challenge facing farmers and other end users of weather and climate information (WCI) in Kenya is the linkage between their perceptions, needs, and engagements with producers of the information. This is highlighted by increased interest in understanding the constraints on appropriate use of weather information by farmers in decision-making. The choice between sub-seasonal and seasonal forecasts can enable better decisions by farmers if the forecast information is reliable and integrated through a cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 146 publications
1
5
0
Order By: Relevance
“…Besides, both husbands and wives reported that weather forecasts are not accurate and dependable, which was confirmed by the finding that weather forecasts were negatively associated with adoption decisions by men. The study by Muita et al ( 2021 ) resonates with our conclusions that farmers’ perceptions of information influenced the choice of CI, while lack of trust, precision, and relevance of CI results in low use of information by farmers in Kenya, but their study overlooked gender perceptive of CIS. However, because there is inherent uncertainty in climate information, events might not always turn out exactly as projected (Tall et al 2018 ).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Besides, both husbands and wives reported that weather forecasts are not accurate and dependable, which was confirmed by the finding that weather forecasts were negatively associated with adoption decisions by men. The study by Muita et al ( 2021 ) resonates with our conclusions that farmers’ perceptions of information influenced the choice of CI, while lack of trust, precision, and relevance of CI results in low use of information by farmers in Kenya, but their study overlooked gender perceptive of CIS. However, because there is inherent uncertainty in climate information, events might not always turn out exactly as projected (Tall et al 2018 ).…”
Section: Discussionsupporting
confidence: 74%
“…Our findings resonate with those of Diouf et al ( 2019 ) in Senegal, who found that men had more access to CIS, but both men and women required timely forecast information, such as the onset of the rainy season. To cope with unpredictable climate risks, Muita et al ( 2021 ) discovered that farmers in Kenya require sub-seasonal and seasonal forecasts with reliable information on rainfall onset dates and distribution. The study also found significant gender-specific preferences in CIS dissemination pathways where husbands preferred receiving climate information through agricultural extension officers, print media, television, and local leaders, whereas the wives mainly preferred radio and social groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical studies among African farmers have shown that seasonal climate forecasts help farmers reduce their vulnerability to drought and climate extremes, while also optimizing their opportunities when favourable rainfall conditions are expected (Awolala, 2018;Roncoli et al, 2009). Several studies have focused on the access and use of weather and climate services for agricultural risk management decision-making in Africa (Alliagbor et al 2020;Awolala et al 2022;Muita et al 2021;Ouédraogo, Ndiaye, and Zougmoré, 2018;Makaudze, 2018;Amegnaglo, Asomanin, and Mensah-bonsu, 2017;Zongo et al, 2016;Limantol et al, 2016;Oyekale, 2015;Rasmussen et al, 2014;Carr et al, 2014;Gebremariam et al, 2013;Mabe et al, 2014;Roncoli et al, 2009Roncoli et al, , 2011Tarhule and Lamb, 2003;Roudier et al, 2011;Zinyengere et al, 2011;Roncoli, Ingram, and Kirshen, 2002). These studies indicate that use of weather information in decision making has substantially benefited farmers.…”
Section: Introductionmentioning
confidence: 99%